Evaluation Of The Efficiency Indicators Of Electric Vehicle Heating Technology In Cold Climate Conditions (Texas Journal of Engineering and Technology, 2026)
This article analyzes the problems of energy losses and reduced range during the operation of electric vehicles in cold climates. The indicators are presented, which are aimed at reducing energy consumption and increasing the overall operational efficiency of the vehicle by evaluating the efficiency indicators of electric vehicle battery heating technologies and optimizing them. The amount of energy consumed during battery heating and its impact on the overall energy balance are estimated using mathematical models. Optimal operating modes for the thermal management system of an electric vehicle battery are developed, and an algorithm for controlling the heating process is proposed. The control algorithm is aimed at maintaining the battery temperature at the required level with minimal energy consumption, and its adaptation to real operating conditions is described in detail.